Long Latency and High Variability in Accuracy-Speed of Prosaccades in Alzheimer’s Disease at Mild to Moderate Stage - Qing Yang; Tao Wang; Ning Su; Yuanyuan Liu; Shifu Xiao; Zoi Kapoula (Dementia and Geriatric Cognitive Disorders Extra, 2011)
Background: Studying saccades is a useful tool to investigate brain function. There is still controversy regarding deficits in prosaccades in Alzheimer’s disease (AD), and a study of saccades in subjects with mild cognitive impairment (MCI) has not been published to date. Methods: We examined horizontal saccades in 10 healthy elderly, and 9 MCI and 9 AD patients. Two tasks were used: gap (fixation target extinguishes prior to target onset) and overlap (fixation stays on after target onset). Eye movements were recorded with the Skalar IRIS system. Results: (1) Latencies were shorter in the gap than in the overlap task (a gap effect) in all three groups of subjects: healthy elderly, MCI and AD; (2) for both tasks, latency of saccades was longer for AD patients than for healthy and MCI subjects, and (3) accuracy and mean velocity were normal in MCI and AD subjects, however, variability in accuracy-speed was higher for AD patients than for healthy and MCI subjects in the overlap task. Conclusions: Abnormalities in reaction time and accuracy-speed variability reflect deficits in cerebral areas involved in the triggering and execution of saccades; a saccade test can be useful to follow up the evolution of MCI subjects as some of them may develop AD disease.